An Analysis of Students’ Motivation in Reading Digital English Textbook at Saiburi Islam Wittaya School in Southern Thailand - Fitriana, Adinda Risma; Anastasia, Faurina; Siregar, M. Riskiyadi (Datokarama English Education Journal, 2025)
The purpose of this study is to identify students' motivation to read English textbooks. In addition, this study also investigates why they have lower motivation in reading English. To explore the research objectives, the researcher used a qualitative research approach with a case study design. To select the participants, purposive sampling technique was used. The participants in this study were 4 female students from different grade levels. Data collection was conducted through observation and interviews. The findings show that there are 3 factors that influence students' motivation in reading English digital textbooks. The three factors are internal factors (intrinsic) students are not interested and feel tired quickly reading digital books, external factors (controlled motivation) students start reading when told by the teacher or with friends, and amotivation students prefer to use printed textbooks rather than digital. These three factors greatly influence students' motivation in reading digital English textbooks. In conclusion, students showed low levels of motivation when interacting with digital English textbooks, both during learning activities and in informal settings during their free time.